On the protective effects of European sustainable stocks during the Russian invasion of Ukraine - Andreas Kick; Horst Rottmann (Ostbayerische Technische Hochschule Amberg-Weiden (OTH), 2024)
Sustainable investments remain popular, attracting investors and researchers alike. Especially the tail-risk properties seem to differ between sustainable stocks and common stocks. Empirically, this can be observed in particular during extreme events. On February 24, 2022 Russian forces invaded Ukraine, thereby marking the beginning of a major historical event. Using standard event study methodology, we analyze if and how Refinitiv's environmental, social, and governance (ESG) ratings, as well as carbon dioxide (CO2) intensity, influence cumulative abnormal returns during different event windows. We find that the abnormal returns of companies with high ecological scores exhibit a protective effect in the pre- and post-event windows. However, this effect did not materialize in all observed event windows. Therefore, our results do not fully support the hypothesis of an 'ESG hedge' against such extreme events.
Keywords: G11; G14; M14; 330; abnormal returns; war; Ukraine; ESG; Russia